RESEARCH OF EFFECT OF PLATELET RICH FIBRIN, PRF ON PARADONTOSIS TISSUES REGENERATION DURING THE EXPERIMENT - О. S. Barylo; Т. М. Kanishyna; А.V. Biloshytska (Ukrainian Medical Stomatological Academy, 2017)
The usage of Platelet Rich Fibrin, PRF means the possibility to apply growth factors in medicine. Growth factors are polypeptides which can stimulate cytodifferentiation, growth, proliferation, and participate in the process of tissue regeneration. Thrombocytes are the natural sources of growth factors. Platelet Rich Plasma PRP, Platelet Rich Fibrin, PRF is used in different branches of medicine. However, there isn't sufficient number of experimental studies related to the usage of PRF to stimulate regeneration of tissue. Purpose To examine the effect of Platelet Rich Fibrin, PRF on the regeneration of paradontal tissues in the experiments with rats. Materials and research methods The set of experiments with 14 rats of both sexes at the age of 12 to 24 months, weigh 170 to 210 g. The animals have been divided into the control group with 5 rats and the experimental group with 9 rats. In the control group the imitated wound of paradontosis has healed on itself, in the experimental group PRF was used. PRF was received by extraction of venous blood of those animals. Blood sampling was conducted on the venous caudal vein. Blood in vitro was distributed into three segments: the upper segment  was plasma with insufficient number of platelets, the middle one was rich with platelets fibrin cake, the lower one was cake of red blood cells. The fibrin was removed from the tube with forceps; red blood cells were cut by a scalpel and placed into the wound. The result of the experiment was evaluated on the 3rd, 7th, 14th days. The morphological research was conducted for PRF efficiency rate. Histological preparations made of PRF and fragments of the lower jawbone, were examined under microscope and photos of them were made. Results The analysis done under microscope of rat's paradontosis tissues has revealed that there is difference between the control and experimental groups. On the 3rd day of treatment around the place of PRF there could be seen the leukocytic infiltration on the wound edges while the leukocytic infiltration of the wound in the control group was less significant. On the 7th day of the experiment the macrophages in the preparations of the rats has appeared, size differed (from small to big cells of irregular form). In addition, in the preparations coloured according to Van-Gizon there appeared collagen tissues. In the control group the macrophages in the wound edges were single, cellular infiltration was not significant. The number of macrophages in the preparations of experimental group of animals was significantly more than in the control group. Conclusion Gradual change of cells-participants is typical for inflammatory process: at first, neutrophilic granulocytes appear in the inflammatory tissue (which also called microphages), then macrophages appear and in the end fibroblasts arise. The main function of macrophages is absorption and resorption of foreign structures. In addition, macrophages transport the inflammatory reaction into fibroblastic stage activating fibroblast proliferation, which generate local matrix, in particular, collagen. Therefore, histological examinations give evidence that the usage of PRF during the course of paradontal treatment leads to fast inhibition of purulent inflammation that promotes the reparative regeneration process. The experiment has been carried out with the small number of animals. Therefore, it was not possible to obtain reliable results. For the further study of this issue the increased number of animals should be engaged into the research.